Metformin-Associated Lactic Acidosis Developed as a Result of a Suicidal Attempt - Vural, Habibe Zehra (Sisli Etfal Hastan Tip Bul, 2020)
Metformin is a biguanide group drug commonly used in the treatment of Type 2 DM. Even though Metformin- Associated Lactic Acidosis (MALA) is not seen very frequently, MALA has a high mortality rate. This case is presented to draw attention to efficiency of hemodialysis and CVVHDF tin the treatment of MALA. A 25-year-old female patient was brought to the emergency service with abdominal pain and confusion. In her detailed history, it was learned that she took 100 tablets of metformin (1000 mg per tablet). Hemodialysis initiated because of severe metabolic acidosis, elevation of blood urea and hyperkalemia were seen in laboratory results. After that, patient was intubated because of low Glasgow Coma Scale (GCS:3) and vasopressor agent were started due to hypotension. In the intensive care unit, blood glucose was seen 44 mg dl(-1) and treated with 10% dextrose solution. CVVHDF treatment was started because of anuria and metabolic acidosis. Patient who underwent CVVHDF treatment for 12-days transferred to nephrology service on the 23(rd) day of the ICU admission with full consciousness and stabilized vitals. In conclusion, hemodialysis and CVVHDF should be the first treatment methods to be considered in patients with metformin-associated lactic acidosis. Renal replacement therapies, initiated rapidly and maintained for an adequate time period are promising in this high mortality rate cases.